تأثير الحقول الكهرطيسية ذات الإشعاعات غير المؤينة لمحطات الخليوي في الإنسان - سميح الجابي; محمد نضال الريس; شحادة مبدا (Tishreen University, 2019)
نظراً للتوسع الكبير في تركيب محطات القاعدة الخليوية فوق أسطح المباني, وظهور تخوف كبير لدى السكان القاطنين بجوار هذه المحطات بسبب تعرضهم للإشعاعات الكهرطيسية التي تبثها الهوائيات من أن تسبب لهم أمراضاً خطيرة. فقد تم التوجه لإنجاز دراسة علمية ميدانية للسكان القاطنين بجوار محطات القاعدة الخليوية المركبة في عدد من أحياء مدينة دمشق, لمعرفة مدى الآثار الصحية التي تحدثها الإشعاعات الصادرة عن هوائياتها, وشملت الدراسة: 1 - إجراء قياسات ميدانية لكل من كثافة الطاقة، وشدة الحقل الكهربائي، وشدة الحقل المغناطيسي للإشعاعات الكهرطيسية الصادرة عن هوائيات محطات القاعدة الخليوية بجوار المباني المركبة عليها هذه المحطات بوصفها تابعاً للمسافة, ومعرفة مدى تعرض السكان لها بجوارها وبعيداً عنها. 2 - إجراء استبيانات إحصائية صحية ميدانية للسكان القاطنين بجوار محطات القاعدة الخليوية وبعيداً عنها؛ لمعرفة مدى الترابط بين الإشعاعات الكهرطيسية الصادرة عنها والأعراض المرضية التي يشكو منها القاطنون بجوارها. ولقد تم التوصل في هذا البحث إلى نتائج علمية مهمة. Given the enormous expansion in the installation of Cellular Base Stations (CBS) on building tops, and the concern of residents, neighbouring those stations, of contracting serious diseases, because of their exposure to electromagnetic radiations, transmitted by (CBS) antennas, a scientific and statistical study has been conducted on residents neighbouring (CBS)s in several quarters of Damascus. The aim of the study is to identify the effect of the CBS's radiation on the human body. The Study involves the following steps: 1. Site measurements have been carried out to evaluate the energy density, the strength of electrical and magnetic fields of the electromagnetic radiation, emitted from the CBS antennas, close to the buildings with (SBC)s on top, taking distance into account, in order to know the range of residents' exposure [to electromagnetic radiation], close to and far away from the CBS's antennas. 2. Field Statistical Health Questionnairs of residents adjacent to -or far away from (SBC)s-have been carried out, in order establish the link between the electromagnetic radiation transmitted by (SBC)s and diseases developed by nearby residents. Finally, very important scientific findings have been obtained.